(untitled) (Fiep Bulletin - online, 2013)
Further to measures of body composition such as weight, height, fat and lean body mass, an excellent structure, composition and shape indicator of the human body is the somatotype technique. Therefore, the aim of this study is to determine the somatotype and anthropometric profile of the Youth football players. The sample was composed by 22 players, male, with a mean age of 18.7±0.8 years, weight of 68.9±5.7 kg and height of 1.79±0.06 m, to the Operario Ferroviário Footbal Club by Youth category, from Ponta Grossa city, Paraná state. The weight, height, skinfold thickness, body circumferences and breadths variables were collected for the purpose of the body composition and somatotype estimating of the players. Body fat calculation (% BF) was established with the body density using the PETROSKI (1995) equation, followed by the application of the Siri (1961) equation. The somatotype was determined according to Heath and Carter (1967). With the data analysis found that the average body fat percentage of the players was 11.2 ± 2.3%. As for somatotypes, it was observed that the athletes had an average feature classified as mesomorph-ectomorph (2,5-3,6-3,3). In others words, there is a predominance of musculoskeletal and linear components (height) relative to the component adiposity. The low percentage of body fat and muscle predominant component observed in the Youth players involved in this study corresponded to the morphological profile of professional athletes in this sport.